A Scale Development Study Regarding the Effects of Organized Industrial Zones on Regional Development: The Organized Industrial Zones Perception Scale - Ahmet Cem Esenlikci; Sedat Murat (Journal of Economy Culture and Society)
One of the most crucial instruments for regional development is organized industrial zones, as these zones contribute to development in many areas, especially regarding the economy and social life in the regions where they are established. This situation has revealed the necessity to investigate the relationship between organized industrial zones and regional development. No single measurement tool has been identified in the literature review to quantify this link. Therefore, this study aims to contribute to the literature by developing a scale to explain the relationship between organized industrial zones and regional development. The sample of the study consists of 600 people aged 18 or over living in the districts where organized industrial zones are located in Trabzon, Türkiye. The programs SPSS23 and AMOS26 are used to analyze the research data. The analysis findings show the scale’s item factor loadings to range between 0.606-0.860, with the total explained variance being calculated as 67.00%. The Organized Industrial Zones Perception Scale is comprised of 21 items and 5 components according to the findings from the confirmatory factor analysis (CMIN / df = 2.824; RMSEA = 0.055; GFI = 0.928; AGFI = 0.905; NFI = 0.923; CFI = 0.949; IFI = 0.949; TLI = 0.939).